The association between motor capacity and mobility performance: frailty as a moderator - Jansen, Carl-Philipp; Toosizadeh, Nima; Mohler, M. Jane; Najafi, Bijan; Wendel, Christopher; Schwenk, Michael (European review of aging and physical activity, 2019)
In older adults, the linkage between laboratory-assessed ‘motor capacity’ and ‘mobility performance’ during daily routine is controversial. Understanding factors moderating this relationship could help developing more valid assessment as well as intervention approaches. We investigated whether the association between capacity and performance becomes evident with transition into frailty, that is, whether frailty status moderates their association.